Analisis Pengaruh Implementasi Program Pemberian Makanan Tambahan Terhadap Keberhasilan Program Penurunan Stunting di Desa Lanji Kabupaten Kendal - Agus Bahrudin (Public Service and Governance Journal, 2025)
Stunting is a serious public health problem in Indonesia. This study aims to analyze the effect of Supplementary Feeding Program (PMT) implementation on the success of stunting reduction programs in Lanji Village, Patebon District, Kendal Regency. The research method uses a quantitative approach with explanatory research type. The research population is families with stunted children totaling 48 respondents using census sampling technique. Data collection used questionnaires, observation, interviews, and documentation. Data analysis used product moment correlation and significance test. The results showed that PMT implementation had a score of 80% (very high category), and success in stunting reduction 73% (high category). Correlation test results show a significant relationship between PMT implementation and stunting reduction success (r=0.61), show that the hypothesis is accepted at a significance level of 5%.